Writing pregnancy in low-fertility Japan - Seaman, Amanda C., 1966- (University of Hawaiʻi Press, 2017)
This text is a wide-ranging account of how women writers have made sense (and nonsense) of pregnancy in postwar Japan. While earlier authors such as Yosano Akiko had addressed the pain and emotional complexities of childbearing in their poetry and prose, the topic quickly moved into the literary shadows when motherhood became enshrined as a duty to state and sovereign in the 1930s and '40s. This reproductive imperative endured after World War II, spurred by a need to create a new generation of citizens and consumers for a new, peacetime nation. It was only in the 1960s, in the context of a flowering of feminist thought and activism, that more critical and nuanced appraisals of pregnancy and motherhood began to appear.